Dipteryx alata, the baru: An analysis of its potential for general use - Verde, Giuliana Vila; Ramos, Jakeline de Oliveira; Oliveira, Marilene Silva; Sousa, Marcos Moreira de; Castro, Joana D’arc Bardella; Peixoto, Josana de Castro; Jesus, Drauton Danillo P. de; Portela, Isleide Alves (Seven Editora, 2023)
Dipteryx alata, popularly known as baru, is a species native to the Brazilian Cerrado. It is a species belonging to the genus Dipteryx alongside 25 other species documented for the genus. The production chain of Dipteryx alata begins with the extractives through the collection and processing that is carried out manually and by hand. Subsequently, the almonds are destined for cooperatives or associations, where the process of roasting, bottling, labeling and sent to trade takes place. However, it is considered a promising species for cultivation, due to its multiple use, establishment of seedlings and high germination rate. The use of baru ranges from the ecological aspect due to its shading potential in the phytophysiognomy in which it is found, through the food, cosmetic and even pharmaceutical importance. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-099